Intensified exposure to compound extreme heat and ozone pollution in summer across Chinese cities - Jingling Su; Limin Jiao; Gang Xu (npj Climate and Atmospheric Science)
Abstract Climate change and air pollution are interconnected global crises, with concurrent heatwaves and extreme ozone levels threatening public health. This study investigates urban population exposure to concurrent extreme heat and ozone pollution across Chinese cities from 2003 to 2020, using high-resolution (1 km) daily temperature and ozone data. We quantify annual exposure rates at national and city levels, distinguishing contributions from urban population growth and compound event frequency. Findings show a 67% increase in compound exposure over 18 years, with 38% of cities, particularly in the North China Plain, exhibiting significant upward trends. Population growth mainly drives exposure in southern cities, while rising event frequency has a greater impact in northern regions. Core urban areas have become critical hotspots, with some major cities’ centers contributing over 80% to total exposure in 2020. The results highlight the urgent need for targeted climate adaptation strategies to mitigate health risks in urban environments.